An EPR and Optical Absorption Study of VO2+ Ions in Di-Ammonium Hydrogen Citrate [(NH4)2C6H6O7] Single Crystals - Karabulut, B.; Tufan, A. (Pergamon-Elsevier Science Ltd, 2008)
Single crystal and powder EPR studies of VO2+ doped di-ammonium hydrogen citrate [(NH4)2C6H6O7] are carried out at room temperature. The angular variation of the EPR spectra show three different VO2+ complexes that are located in different chemical environment, and each environment contains two magnetically inequivalent VO2+ sites in distinct orientations occupying substitutional positions in the lattice. Crystalline field around the VO2+ ion is nearly axial. The optical absorption spectrum shows two bands centred at 16,949 and 12,345 cm-1. Spin Hamiltonian parameters and molecular orbital coefficients are calculated from the EPR and optical data, and results are discussed. © 2007.
Keywords: DAHC; Di-Ammonium Hydrogen Citrate; EPR; Metal Ions; Optical Absorption; VO2+